Systemization of a pharmacy technician career ladder in a multi-hospital system - Niaz Deyhim; Sunny B. Bhakta; Alex C. Varkey; Daniel L. Metzen; Divya Varkey; René J. Martinez; Kevin W. Garey (Elsevier, 2021)
Purpose: Hospital consolidation into larger, systemized health systems has enabled system-wide standardization of promotion processes, including pharmacy technician career ladders. However, whether system standardization affects the job satisfaction or outcomes of pharmacy technicians is unknown. The purpose of this project was to assess pharmacy technician perceptions and outcomes after systemization of a pharmacy technician career ladder. Methods: Pharmacy technician satisfaction scores and outcomes (promotion and turnover rates) were assessed in an eight-hospital health system before and after systemization of a pharmacy technician career ladder. Results: Two hundred and forty-nine pharmacy technicians were employed during the pre-intervention (n = 104) and post-intervention (n = 145) time periods. One hundred and twenty-three of 145 (84.83%) pharmacy technicians completed a job satisfaction survey after implementation of the system-wide technician career ladder. Overall satisfaction for the career ladder averaged 3.8 ± 0.61 or between neutral to positive satisfaction. There was no difference in total satisfaction regardless of teaching (3.8 ± 0.59) or community hospital (3.8 ± 0.63) location (p = 0.53) or stratifying by Pharmacy Technician status. A total of 50 pharmacy technicians were hired during the study period, either during the pre-implementation (n = 36) or post-implementation (n = 14) time periods. Time to the first promotion averaged 1.73 ± 1.00 years in the pre-implementation period and 1.36 ± 0.55 years in the post-implementation period (p = 0.20). Technician voluntary turnover was similar between the time periods. Conclusion: In conclusion, the standardization of a systems-level pharmacy technician promotion ladder from a single hospital to a systems-level was associated with positive job satisfaction and similar promotions and turnover rates as the historic, single hospital-based promotion ladder.